Analysis of the distribution of rice allergens in brown rice grains and of the allergenicity of products containing rice bran. (15th March 2019) - Satoh, Rie; Tsuge, Ikuya; Tokuda, Reiko; Teshima, Reiko
Highlights: The distribution of rice allergens in brown rice grains were examined. The allergenicity of cosmetics and health foods containing rice bran were analyzed. The 52-kDa globulin was found in rice bran and products containing rice bran. The 52-kDa globulin is the most likely causative allergen of rice bran allergy. Abstract: To understand the allergenicity of rice bran, the distribution of rice allergens in brown rice grains was analysed and the allergenicity of cosmetics and health foods containing rice bran determined. RAG2 and a 19-kDa globulin were localized in polished rice, while a 52-kDa globulin was localized in rice bran. The 52-kDa globulin was also identified as the most likely causative allergen of rice bran allergy. Several products containing intact rice bran were found to contain the 52-kDa globulin. Our study provides the first data regarding cosmetics and health foods containing potential rice bran allergens. Western blot analysis using a rice-bran-allergic patient's plasma showed that 52-kDa globulin was detected as an IgE-binding protein of rice bran and some rice bran-containing cosmetics and health foods. Our results indicate that patients with rice bran allergy need to be careful about using products containing intact rice bran as a constituent.